2008
DOI: 10.1080/11263500802151058
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the response of poplar (Populus nigra) roots to mechanical stress imposed by bending

Abstract: Mechanical stress is a widespread environmental condition that can be caused by several factors (i.e. gravity, touch, wind, soil density, soil compaction and grazing, slope) and that can severely affect plant stability. In response to mechanical stress and to improve their anchorage, plants have developed complex mechanisms to detect mechanical perturbation and to induce a suite of modifications at anatomical, physiological, biochemical, biophysical and molecular level. Although it is well recognized that one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 102 publications
1
32
1
Order By: Relevance
“…One-year-old Populus nigra seedlings (Alasia Franco Vivai, Savigliano (CN), Italy; http://www.alasiafranco.it/) were subjected to mechanical stress by bending their taproots around a 90°angle curved steel net, as described in our previous studies (Scippa et al 2008;Trupiano et al 2012b). Thirty plants with bent roots, together with the same number of plants with taproots linked to a vertical steel net (control, C), were grown under controlled water regime and natural photoperiod and temperature.…”
Section: Plant Materials and Mechanical Stress Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One-year-old Populus nigra seedlings (Alasia Franco Vivai, Savigliano (CN), Italy; http://www.alasiafranco.it/) were subjected to mechanical stress by bending their taproots around a 90°angle curved steel net, as described in our previous studies (Scippa et al 2008;Trupiano et al 2012b). Thirty plants with bent roots, together with the same number of plants with taproots linked to a vertical steel net (control, C), were grown under controlled water regime and natural photoperiod and temperature.…”
Section: Plant Materials and Mechanical Stress Treatmentmentioning
confidence: 99%
“…In woody plants, on the other hand, root response to mechanical stresses has been mostly investigated at the morphological, biomechanical and anatomical level, whereas studies focused on molecular mechanisms are still scarce. In a previous work, we used a right-angle curved steel net to induce a long-term mechanical stress response in woody taproot of poplar (Populus nigra L.) and found that different intensity of tension and compression forces and the direction of gravity can elicit specific responses such as lateral roots emission and reaction wood formation (Scippa et al 2008;Trupiano et al 2012aTrupiano et al , b, 2014. Furthermore, using this experimental system we analyzed spatial and temporal changes in the root proteome and in hormone levels (Trupiano et al 2012b(Trupiano et al , 2014.…”
Section: Introductionmentioning
confidence: 98%
“…from branches, broken and partly buried trunks, excavated roots). Recent proteomic analyses have shown that poplars have developed complex biochemical mechanisms to detect mechanical constraints such as those imposed by water flow and sediment burial and to induce specific responses improving their anchorage (Scippa et al, 2008;Trupiano et al, 2012). Vegetative propagation represents a defense mechanism to mechanical constraints, submersion and sediment burial.…”
Section: Key Phases Of the P Nigra Biogeomorphological Life Cycle (Blc)mentioning
confidence: 99%
“…Chemical ecology or ecological stoichiometry (Sterner and Elser, 2002) and metagenomics (Marco, 2010) may also become useful in the near future to identify respectively characteristic chemical (e.g. Many of these trait loci have already been mapped (Yin et al, 2004), for example, those related to the response of poplar roots to mechanical stress imposed by bending (Scippa et al, 2008;Trupiano et al, 2012). At the molecular level, the role of intraspecific genetic variability of P. nigra populations related to engineer traits must be defined in order to quantify the variability in abiotic responses (e.g.…”
mentioning
confidence: 99%
“…In particular, proteins with altered synthesis due to changes in gene expression may be used to design molecular markers for the selection of genotypes (Kieffer et al 2009, Regier et al 2009, Visioli et al 2010). However, Scippa et al (2008) have studied the complex mechanism involved in the reaction of root biology to environmental stress. In particular, Trupiano et al (2012a) have observed functional and structural changes in roots, which emitted new laterals and increased biomass and lignin synthesis under mechanical stress.…”
Section: Breeding For Phytoremediationmentioning
confidence: 99%